Necesidad de incorporar en el libro tercero del Código Orgánico Integral Penal, el órgano encargado para la ejecución de las sentencias en cumplimiento de las penas de los entes empresariales - Pino Gonzaga, Ruth Elina (2015)
The Code of Integrated Criminal establishes corporate criminal responsibility, which is set for a group of crimes that says the same legislation, actions or crimes that endanger social economic order and the environment, as a supranational legal rights. Among the responsibilities in criminal law, individuals were, but there was no criminal liability to corporate entities, to put into effect the new comprehensive criminal law, where the act of a company is subject to criminal prosecution of certain crimes they can commit their legal representatives, out of civilians that occurred, by the act of the company, crimes that have their own sanctions on certain of that legislation, such as fines, criminal forfeiture, temporary closure or definitive of shares premises or facilities, activities for the benefit of the community subject to monitoring, comprehensive remediation of environmental damages and a ban on state contracts with temporary or permanent. According to the new criminal law legal persons are likely to determine their responsibility for their actions when the actions of these people have produced containing effects for the same crimes, thus subject to a criminal. Art. 71 of the Code of Criminal Integral establishes penalties for legal persons, such as fines, criminal forfeiture, temporary or permanent closure of premises or facilities, activities for the benefit of the community subject to monitoring, comprehensive remediation environmental damage and prohibition of contracting with temporary or permanent state. The penalties for natural persons are applicable, which marks the third book of this Comprehensive Organic Penal Code dealing with the execution, but nothing in this book expresses the sanctions imposed on legal persons, the body responsible for enforcement of penalties for corporate bodies, causing legal uncertainty in its application to criminal punishment